The relationship between anxiety and parent-child attachment and psychological resilience among Chinese college students: take 100 thousand college students as sample - Li, Zhe; Zhao, Yu-Yu; Li, Xin; Liu, Ke; Tian, Dong-Hua; Li, Su-Xia; Zhang, Xiang-Yang (Frontiers in Psychiatry, 2026)
BackgroundPrevious studies on the relationship between good parent-child attachment, psychological resilience with mental health, have limitations such as small sample sizes and specific regions or universities, which lack universality. This study aims to survey a total of 100,253 college students across China to clarify the correlation between parent-child attachment, psychological resilience and mental health among college students.MethodsOnline questionnaires were performed from April 13 to 23, 2020 in China, used 10-item Depression Self-Rating Scale, Generalized Anxiety Disorder Scale (GAD-7), Resilience Scale-Simplified (CD-RISC-10), and Parental Attachment Items in the Parent-Peer Attachment Scale (IPPA).ResultsIn total, 100,253 university students completed this survey. The detection rate of anxiety symptoms and depression symptoms were 42.74% and 44.25%, respectively. The parent-child attachment and psychological resilience among them were in a medium level. Anxiety symptoms, rather than depression symptoms were closely related to the quality of parent-child attachment and psychological resilience. However, there was no correlation between depression scores and parent-child attachment, as well as psychological resilience.ConclusionOur findings indicate that both depression and anxiety symptoms in college students’ population are high, and suggest that college students may have different etiology and pathogenesis of depression and anxiety. The treatment strategies for these two different types of symptoms for college students’ population, especially the psychological treatment strategies, should be differentiated accordingly.